A Critical Review Of The Impact Of Health Policies On The Realization Of The Right To Health For Women - Monalisha Singh, Aastha Choudhary, Snehil Raj, Umang Sagar, Rohit Sinha, Gaurav Kumar, Sumit Kumar (South Eastern European Journal of Public Health, 2025)
The right to health is a fundamental and universally recognized human right, enshrined in international treaties, national constitutions, and legal frameworks, ensuring that every individual has access to the highest attainable standard of physical and mental well-being. However, women’s health rights remain a critical issue globally, as gender-specific disparities continue to persist due to socio-economic, cultural, and political factors. This paper provides a critical review of the impact of health policies on the realization of the right to health for women, examining the extent to which national and international legal frameworks have successfully addressed gender-based health inequities. Women’s health needs are distinct and multidimensional, encompassing reproductive and maternal healthcare, access to contraception, safe abortion services, menstrual health management, prevention and treatment of gender-based violence, and gender-sensitive approaches to non-communicable diseases. However, various structural barriers—including discriminatory laws, inadequate funding, lack of political will, and social stigma—undermine the effective implementation of health policies. While global health policies, such as those established by the World Health Organization (WHO) and the United Nations Sustainable Development Goals (SDGs), emphasize gender equality and universal health coverage, their practical enforcement remains inconsistent across different socio-economic and legal landscapes. The paper critically evaluates the interplay between international human rights instruments such as the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW), the International Covenant on Economic, Social and Cultural Rights (ICESCR), and national health policies in different countries. By analyzing case studies from diverse geographical regions, the study highlights both the progress made and the challenges that persist in ensuring women’s access to equitable healthcare services. It further explores the disparities in healthcare access for women from marginalized and vulnerable communities, including those in rural areas, indigenous populations, refugees, and women with disabilities, demonstrating how intersectionality plays a crucial role in determining health outcomes. A significant portion of the analysis is dedicated to examining how economic policies—such as healthcare privatization, user fees, and out-of-pocket expenditure—affect women’s ability to access healthcare. The increasing commercialization of healthcare has disproportionately affected women, particularly those in lower-income groups, as they often bear the financial burden of medical expenses for themselves and their families. The study also investigates the impact of global health crises, such as the COVID-19 pandemic, which exposed pre-existing weaknesses in health systems and resulted in significant disruptions to essential services such as maternal and reproductive healthcare. Moreover, this paper critically assesses the effectiveness of legal and policy interventions aimed at improving women’s health rights. It examines best practices from countries that have successfully implemented gender-responsive health policies and draws comparisons with nations where restrictive laws and inadequate policy frameworks continue to hinder progress. The role of civil society organizations, advocacy groups, and grassroots movements in influencing policy changes and holding governments accountable is also explored, highlighting the power of collective action in advancing women’s health rights. In conclusion, the research underscores the urgent need for comprehensive, inclusive, and well-implemented health policies that address systemic gender-based disparities. A human rights-based approach to healthcare, which integrates legal protections, financial accessibility, and community-driven solutions, is essential for ensuring that women’s health rights are fully realized. Governments and policymakers must prioritize intersectional and gender-sensitive strategies, increase investments in women’s health, and strengthen legal mechanisms to eliminate discrimination and ensure accountability. Ultimately, this paper calls for a transformative shift in health policy frameworks, emphasizing the importance of equity, justice, and the right to health as a fundamental pillar of women’s empowerment and well-being.